RADT-05. PROSPECTIVE LONG-TERM EVALUATION OF MRI- AND CLINICAL CHANGES FOLLOWING STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASES – IS REPEAT SRS A CONSEQUENCE, OR ALSO A CAUSE OF LONG-TERM SURVIVAL?. (12th November 2021) - Skeie, Bente; Enger, Per Øyvind; Skeie, Geir Olve; Heggdal, Jan Ingemann
Abstract: The use of stereotactic radiosurgery (SRS) for brain metastases are increasing. Response assessment is challenging and the clinical significance of radiological response and retreatments are poorly defined. Ninety-seven patients with a total of 406 brain metastases were followed prospectively for 10 years or until death. Volume changes over time and clinical outcome in response to first time SRS and SRS retreatments were analyzed. Tumors grew significantly before (p = 0.004), but shrunk at 1 and 3 months (p = 0.001) following SRS. Four response-patterns of were observed; tumors either continuously reduced in size (A, 62%), pseudo-progressed (PP, B, 13%), temporarily reduced in size (C, 24%), or grew continuously (D, 2%); corresponding to 75% local control (LC) at initial SRS. Predictors for LC were primary cancer site (p = 0.001), tumor volume (p = 0.002) and target cover ratio (p = 0.005). Subsequent SRS for new lesions resulted in 94% LC (87% A) and repeat-SRS for local failures in 80% LC (57% B), predicted by higher prescribed dose, p = 0.001 and p = 0.042, respectively. Overall survival was only 4.5 months if A-response for all lesions, 13.3 months if at least one B-response, 17.1 months if retreated C- or D-response (p < 0.001), (7.5 and 4.7 months if untreated). Quality of life (p = 0.003), steroid use (p = 0.019) and prior whole brain radiotherapy (p = 0.026) were predictors for survival. There are 4 response patterns to SRS predicted by tumor size, primary cancer site, target cover ratio and prescribed dose. Long-term survivors experienced a higher incidence of PP and were more often retreated for new lesions and local failures. The immune response induced by PP seems beneficial but further studies are needed.